Subseasonal Variation of 2020 Meiyu Rainfall With Extremely Long Duration Over the Yangtze–Huaihe River Basin in China - Chen, Shengjie; Kang, Zhiming; Liu, Mei; Lv, Runqing; Ma, Jing; He, Jinhai (Frontiers in Earth Science, 2022)
An observed fact is proposed that the 2020 recordbreaking Meiyu over the YangtzeHuaihe River Basin (YHRB) is characteristic of significant subseasonal variation. The anomalously enhanced rainfall experiences a southward retreat from the northern YHRB in June to the southern YHRB in July. The meridional shift of abnormal rainbelt is closely related to the different anomalous Meiyu front circulations. The first stage features a warm Meiyu front with an extremely strong northward transport of warmandwet air, while a cold front forms with a convergence between the strong northeasterlies and southwesterlies in July. Another significant subseasonal variation of the 2020 Meiyu is that the Meiyu rainfall evolves in a periodic quasibiweekly oscillation (QBWO). On the scale of the QBWO, the cold air activities over East Asia contribute significantly to Meiyu; each intense southward invasion of cold air corresponds well to the enhancement of Meiyu rainfall. However, the location of the western Pacific subtropical high (WPSH), the subtropical East Asian summer monsoon (SEASM) and the intensity of the East Asian subtropical westerly jet (EASWJ) exhibit opposite QBWO characteristics in June and July. For an increasing (decreasing) of Meiyu rainfall, the WPSH marches northward (retreats southward); the SEASM weakens (strengthens); and the EASWJ accelerates (decelerates) in June. The opposite holds true in July. Further analyses reveal that the filtered cyclone over Northeast China benefiting the southward intrusion of cold air is associated with the eastward propagation of a wave train over the midhigh latitudes in June, while it arises from both the westward propagation of a wave train over the midhigh latitudes and the northward propagation of cyclonic circulation from the tropics in July.